(untitled) (Journal of Educational Sciences, 2020)
The researchers conducted a comparative analysis of methods for measuring the spiritual and moral values of Kazakhstan and Finland. The methods of measuring the values of one of the leading researchers in different countries on the example of youth are given. Today, Kazakhstan is one of the most progressive and fast developing countries. This progressive development leads the country not only to the better economy but also to the social and cultural changes in civilian’s life. It can be seen in lives of younger people and their forming values of morality. The maintained traditions of centuries, allowed people to create conventional values such as: respect for older people, love towards the motherland, worship of ancestors etc. However, the 21st century has it own conditions, where the spirituality is different from religion, morality is now measured by new factors, and where older upbringing methods are now replaced by newer, evaluated forms of it. The survey presented by the author, describes us the connection between spiritual intelligence, religious concept and the attitude towards morality and self acceptance of younger generations. The comparative analysis of Kazakhstan and Finland, shows the reciprocity in terms of moral changes and values, despite the country differences. Globalization, expansion of the frontiers results in such changes.